2023
DOI: 10.1097/j.jcrs.0000000000001211
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the astigmatism-reducing effect of toric intraocular lenses in eyes with low astigmatism: randomized masked bilateral comparison

Abstract: Purpose: To evaluate the astigmatism-reducing effect of toric intraocular lenses (IOLs) for low amounts of corneal astigmatism. Setting: Hanusch Hospital, Vienna, Austria. Design: Randomized, masked, controlled trial with bilateral comparison. Methods: Patients scheduled for bilateral cataract surgery and a corneal astigmatism in both eyes between 0.75 diopters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Professor Oliver Findl, from the Karl-Landsteiner Institute in Austria, had the highest h-index. His research directions include the efficacy and safety of various ophthalmological methods and IOLs, including an exploration of the characteristics of online IOL calculation tools [ 36 ] , and evaluation of the astigmatism-reducing effect of toric IOLs for low amounts of corneal astigmatism [ 37 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professor Oliver Findl, from the Karl-Landsteiner Institute in Austria, had the highest h-index. His research directions include the efficacy and safety of various ophthalmological methods and IOLs, including an exploration of the characteristics of online IOL calculation tools [ 36 ] , and evaluation of the astigmatism-reducing effect of toric IOLs for low amounts of corneal astigmatism [ 37 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The last cluster encompassed astigmatism and toric IOLs. Toric IOLs are considered the most productive way of correcting corneal astigmatism in a patient undergoing cataract surgery [ 60 ] ; thus, some studies have explored different aspects of toric IOLs in astigmatism correction [ 37 , 60 , 61 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The 3 RCTs were published in 2023, 12 2021, 13 and 2020. 14 One prospective study published in 2023 16 and 6 retrospective studies were published between 2021 and 2023.…”
Section: Methodsmentioning
confidence: 99%
“…This report includes 1 SR, 11 3 RCTs, [12][13][14] and 7 nonrandomized studies (1 prospective and 6 retrospective). [15][16][17][18][19][20][21] Additional details regarding the characteristics of the included publications are provided in Appendix 2.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…Studies have demonstrated that the refractive outcomes of these eyes are better than those receiving only spherical IOLs. Recent work by Heinert et al [ 45 ] illustrated that toric IOLs can effectively reduce low astigmatism (ranging from 0.75 to 1.5D) and significantly improve visual acuity as compared to non-toric IOLs. However, given the premium cost of toric IOLs, a cost-benefit analysis of low-powered toric IOL implantation remains to be further explored [ 46 ].…”
Section: Correction Of Low Astigmatismmentioning
confidence: 99%